DETERMINANT OF REGIONAL FINANCIAL INDEPENDENCE: REGENCY/CITY GOVERNMENT AT SOUTH SUMATRA PROVINCE - Tri Somadi,Rita Martini,Firmansyah,Lambok Vera Riama Pangaribuan,Kartika Rachma Sari,Rulyanti Susi W (International Conference on Industrial Revolution for Polytechnic Education, 2019)
This study aims to determine whether the regional wealth, natural resources revenue sharing fund and general allocation fund to the independence of regional finance at the government of regency/city in South Sumatra Province. The population in this study is all of regency/city in the Province of South Sumatra. Sample determination is determined by purposive sampling technique as many as 17 regencies/cities in South Sumatra Province consisting of 13 districts and 4 cities. The type of research is quantitative research with secondary data. Form the Budget Realization from the Audit Result Report (LHP) BPK RI in the period 2014-2016.The analytical method used is multiple linear regression analysis with panel data. The results showed that the regional wealth and general allocation fund partially influenced the direction of positive relationship to regional financial independence. While natural resources revenue funds partially influence with the negative direction towards the regional financial independence. Simultaneously regional wealth, natural resources revenue funds and general allocation fund simultaneously have a significant effect on regional financial independence at the government of regency/city in South Sumatra Province